The Difference a Job Makes: Licit and Illicit Work Experiences and Aspirations at a Transitional Housing Facility for Women Leaving the Sex Industry. Issue 2 (4th March 2019) - Hankel, Jennifer; Brown, Kyria; Dewey, Susan; McKinnon, Caroline
Abstract : This investigation establishes a baseline understanding of how women exiting the sex industry understand the economic options available to them by reviewing their work experiences in the legal economy, histories of sex industry involvement, and their aspirations for legal work upon entering a yearlong residential program offered at a transitional housing facility. Specifically, it explores how prior work experience, type of sex industry involvement, and demographic characteristics such as race and age intersect with women's legal work aspirations upon leaving the sex industry. Analysis indicates that women's occupational choices are limited by prior experiences within the formal and informal economies and that women of color and poor women of all ethno-racial backgrounds are particularly likely to face disadvantages in both economic sectors. Findings accordingly indicate that rehabilitative settings must consider whether the career pathways they create lead to economic self-sufficiency and reduce the likelihood that women will return to life situations they express a desire to leave.